Cross-sectional analysis of e-cigarettes, combustible tobacco and their dual use with binge drinking among college students in the USA - Fares Qeadan; Rose Thornquist (BMJ Public Health)
Background Tobacco use is a long-standing epidemic that has caused millions of premature deaths. Electronic cigarette use is rising among young adults, yet few studies have included combustible tobacco, e-cigarettes and their dual use in an analysis of binge drinking among college students. This study aims to calculate the associations between these three forms of tobacco use and binge drinking among college students.Methods This cross-sectional study used data from 332 721 college students from the American College Health Association-National College Health Assessment survey. Tobacco use was organised into four groups: no tobacco use, e-cigarette use only, combustible tobacco use only and dual use of e-cigarettes and combustible tobacco. Binge drinking was a binary indication of whether students had engaged in binge drinking in the last 2 weeks. Multiple logistic regression was employed to examine the relationship between tobacco use and binge drinking, adjusting for demographic factors and constructs of the integrated behavioural model.Results Each tobacco use group had significantly higher odds of binge drinking compared with students who did not use tobacco. Students who engaged in dual tobacco use had significantly higher odds of binge drinking compared with exclusive combustible tobacco use (adjusted OR, aOR=2.41, 95% CI: 2.29, 2.53) and exclusive e-cigarette use (aOR=1.79, 95% CI: 1.71, 1.86).Conclusion The strong relationship between dual tobacco use and binge drinking among college students warrants further investigation into the aetiology and clinical manifestations of this emerging coupled substance use behaviour among the next generation of adults.